Indonesian SMEs' Competitive Advantage Through Organizational Agility: The Role of Information and Communication Technologies (ICT) To Small Business - Heriyanto, Meyzi; Febrian, Achmad Fajri; Karneli, Okta; Sugiarto, Meilan; Suryana, Dodi (Journal of Ecohumanism, 2024)
The research objective analyzes competitive advantage through small business organizational agility through Information and Communication Technology (ICT) capabilities as an effort to increase competitive advantage. This study uses purposive sampling as a data collection technique; meanwhile, Structural Equation Modeling (SEM) with smartPLS software was employed as the data analysis technique. The data collection method is carried out through survey techniques by distributing questionnaires to respondents with random sampling. The number of 388 small business actors were treated as research respondents. Results showed that ICT capabilities contributed significantly to competitive advantage either directly or through the moderating variable of organizational agility. By integrating ICT as an antecedent variable, further research can focus on the factors determining the transformation of small businesses into medium and large businesses. Additionally, while ICT capability directly affects competitive advantage, its indirect impact, specifically via the business agility variable, is usually smaller. Therefore, business agility strengthens the indirect relationship between ICT capabilities and competitive advantage.